A metamorfose em Claude Crébillon - Ana Alexandra Seabra de Carvalho (Carnets, 2013)
In this paper we will study the meanings of metamorphosis in four narratives by Claude Crébillon: Le Sylphe, ou Songe de Madame de R*** écrit par elle-même à Madame de S*** (1730); L’Écumoire ou Tanzaï et Néadarné. Histoire japonoise (1734); Le Sopha. Conte moral (1742); and Ah Quel Conte! Conte politique et astronomique (1754). As a fairy tales teller, the author gets back to and transforms a wide cultural background where different fairy-like traditions meet. Several meanings of metamorphosis will be considered here either as an aesthetic-literary process questioning fairy tales exoticism of coeval literature, either as a recreational and transgressor method to criticize excessively hedonistic morals and behaviour as well as political manoeuvres. Thus, in these works, the process of metamorphosis serves the critical vision over literature and society dear to Crébillon.